Twin-Twin transfusion syndrome: a case report - Bansal, Romi; Kaur, Jasleen; ., Priyanka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Twin to twin transfusion syndrome is a rare but serious complication of monochorionic twin pregnancy. It is characterized by the development of abnormal placental vascular communication from one foetus (donor) to the other foetus (recipient). If left untreated it led to high rates of perinatal morbidity and mortality due to its poorly understood etiology and difficulty in diagnosing and treatment. Authors report a case of twin to twin transfusion syndrome in 24 years old primigravida with gestational age of 18 weeks 5 days diagnosed on ultrasound.